PEMAFAATAN PATI SAGU DAN TEPUNG KELAPA DALAM PEMBUATAN KUE BANGKIT - Fitri ' Afrianti; Raswen ' Efendi; Yusmarini ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Kue Bangkit (tapioca cookies) is a typical Malay traditional cookie. They are generally made using the basic tapioca ingredients similar to sago starch. The Making of tapioca cookies uses the basic materials of sago starch and coconut flour. This study aims to discover the effect of the use of sago starch and coconut flour on the quality of tapioca cookies and to set the best formulation. The study uses a completely randomized design (CRD) with five treatments and four repetitions. The data were processed using Annova test with which  if any influence is found then DNMRT test is taken at 5% level. The treatment of formulation applied on tapioca cookies SK1: Sago starch 90% with coconut flour 10%, SK2: sago starch 80% with coconut flour 20%, SK3: sago starch 70% with coconut flour 30%, SK4: sago starch 60% with coconut flour 40%, SK5: sago starch 50% with coconut flour 50%. The results showed that the addition of sago starch and coconut flour has significant effect (P <0.05) on water content, protein content of organoleptic testing, texture, flavors, aroma and hedonic. But it has no significant effect (P> 0.05) on ash content. Thus, it can be concluded that the best quality of tapioca cookiesis obtained from the formulations of 70% sago starch and 30% coconut flour (SK2), which have met the standard of cookies in Indonesia SNI (01-2973-1992).  Keyword : Sago starch , coconut flour, cookies.